SEMANTIC AND CROSS-CULTURAL SHIFTS IN TRANSLATING THE INDONESIAN FILM TITLE ABADI NAN JAYA INTO THE ELIXIR - Debora Afriyanti Siadari (Jurnal Media Akademik (JMA), 2026)
Film title translation involves not only linguistic transfer but also cultural negotiation shaped by differing communication styles and audience expectations. This study examines the semantic and cross-cultural shifts that occur in the translation of the Indonesian film title Abadi Nan Jaya into its English version, The Elixir. Employing a qualitative descriptive approach, the research analyzes the lexical components of both titles through dictionary definitions, etymological references, and cross-cultural communication theories, particularly Hall’s high- and low-context framework and Hofstede’s cultural dimensions. The findings reveal a substantial shift from an abstract, morally embedded expression rooted in Indonesian collectivist and high-context culture to a concrete, object-oriented concept aligned with the explicit communication preferences of low-context, individualist audiences. While Abadi Nan Jaya conveys notions of collective resilience, moral continuity, and spiritual triumph, The Elixir foregrounds a tangible narrative element that ensures immediate clarity and international accessibility. This transformation demonstrates how translation strategies may simplify or redirect culturally embedded meanings to meet global market expectations. The study highlights that film title translation functions as a process of cultural mediation, balancing the preservation of local identity with the demands of global comprehensibility and marketability.